The Association Between Sarcopenia and Functional Improvement in Older and Younger Patients Who Completed Inpatient Rehabilitation: A Prospective Cohort Study - Churilov, Irina; Churilov, Leonid; Brock, Kim; Murphy, David; MacIsaac, Richard J.; Ekinci, Elif I. (Frontiers in Rehabilitation Sciences, 2021)
Objective: To investigate the association between sarcopenia and functional improvement in patients older and younger than 65 years upon completion of an inpatient rehabilitation program. Design: Prospective cohort study. Participants: Adult consecutive patients who completed the inpatient rehabilitation program at a metropolitan tertiary referral hospital general inpatient rehabilitation unit. Methods: Sarcopenia status was determined using the European Working Group on Sarcopenia in Older People 2 algorithm. Progress in rehabilitation was measured using change in the Functional Independence Measure and Goal Attainment Scaling score. Results: 257 participants (128 (50%) male, median age 63 years (IQR: 52-72)), 33(13%) with sarcopenia, completed inpatient rehabilitation (median length of stay 16 days (IQR: 11-27.5)). Participants’ median Functional Independence Measure change was 24 (IQR 15-33.5) and mean total Goal Attainment Scaling score was 57.6 (SD 10.2). Adjusting for admission Functional Independence Measure score, the median difference in Functional Independence Measure change between participants with and without sarcopenia was: -4.3 (95%CI: -10.6,1.9); p=0.17 in participants 65 years and younger, and 4.6 (95%CI: 1.0,8.2); p=0.01 in participants older than 65; age-by-sarcopenia interaction p =0.02. Conclusions: Unlike younger people, older people with sarcopenia have greater functional improvement in inpatient rehabilitation than those without sarcopenia.